Nitrogen and Phosphorus Dual-Doped Graphene/Carbon Nanosheets as Bifunctional Electrocatalysts for Oxygen Reduction and Evolution - Li, Rong; Wei, Zidong; Gou, Xinglong (ACS catalysis, 2015)
It is highly desirable but challenging to develop bifunctional catalysts for efficiently catalyzing both the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in energy storage and conversion systems. Here a simple yet cost-effective strategy is developed to fabricate nitrogen and phosphorus dual-doped graphene/carbon nanosheets (N,P-GCNS) with N,P-doped carbon sandwiching few-layers-thick graphene. The as-prepared N,P-GCNS shows outstanding catalytic activity toward both ORR and OER with a potential gap of 0.71 V between the OER potential at a current density of 10 mA cm–2 and the ORR potential at a current density of −3 mA cm–2, illustrating that it is the best metal-free bifunctional electrocatalysts reported to date. The superb bifunctional catalytic performance is attributed to the synergistic effects between the doped N and P atoms, the full exposure of the active sites on the surface of the N,P-GCNS nanosheets, the high conductivity of the incorporated graphene, and the large surface area and hierarchical pores for sufficient contact and rapid transportation of the reactants.